A Critical and Exegetical Commentary on Galatians - Tuckett, Christopher M. (The International critical commentary on the Holy scriptures of the Old and New Testaments, 2024)
Cover -- Title Page -- Copyright -- Contents -- General Editors' Preface -- Preface -- Abbreviations -- Bibliography -- Introduction -- 1. Authorship, Prolegomena -- 2. Addressees -- 3. Date -- 4. The 'Opponents' in Galatians -- 5. Rhetoric, Genre and the Structure of Galatians -- 6. Text and Canon -- 7. Reception -- Commentary -- 1.1-5. Opening Greetings -- 1.6-10. The Galatians Rebuked: The Reason for the Letter -- 1.11-2.21. The Origin and Nature of Paul's Gospel -- 1.11-17. The Divine Origin of Paul's Gospel -- 1.18-24. Paul's First Visit to Jerusalem and its Aftermath -- 2.1-10. Paul's Second Visit to Jerusalem: The Apostolic Council -- 2.11-14. The Incident at Antioch -- 2.15-21. Paul's Gospel - for Antioch and Galatia -- 3.1-4.7. Arguments against the Demand for Circumcision -- 3.1-5. Appeal to the Galatians' Experience of the Spirit -- 3.6-14. Appeal to Abraham in Scripture -- 3.15-18. Appeal to Analogy: Law and Inheritance -- 3.19-25. The Purpose of the Law -- 3.26-29. Appeal to Christian Tradition -- 4.1-7. Appeal to the Spirit: Slaves, Sons and Heirs -- 4.8-20. Personal Appeals to the Galatians -- 5.1-6. On Christian Freedom -- 5.7-12. Against the Agitators -- 5.13-6.10. Flesh and Spirit -- 5.13-6.2. The Ethical Demands of Life in the Spirit -- 6.3-10. Further Exhortations -- 6.11-18. Final Words and the Ending of the Letter.